Impact of acute and chronic exposure to sulfamethoxazole on the kinetics and microbial structure of an activated sludge community - Pala-Ozkok, Ilke; Katipoglu-Yazan, Tugce; Olmez-Hanci, Tugba; Jonas, Daniel; Ubay-Cokgor, Emine; Orhon, Derin (Frontiers in Antibiotics, 2024)
The aim of this study was to uncover microbial and kinetic impact of acute and chronic exposure to one of the frequently administered antibiotics sulfamethoxazole on the activated sludge biomass. Respirometric analysis and model evaluation of the oxygen utilization rate profiles was the backbone of this study. They showed that, continuous exposure to sulfamethoxazole resulted in inhibition of substrate storage and increase in endogenous decay rates by 2 folds, which was supported by the resistance gene analysis. Additionally, a mild inhibition on the growth and hydrolysis kinetics was observed. Moreover, sulfamethoxazole had a binding impact with available organic carbon resulting in slightly less oxygen consumption. DNA sequencing and antibiotic resistance gene analyzes showed that continuous exposure to sulfamethoxazole caused a change in the community structure at species level. Resistant bacteria like Arthrobacter sp and members of Chitinophagaceae and Intrasporangiaceae families were found to be dominating the bacterial community. Impact of intermittent exposure was also investigated, and the results indicated a drop in the severity of the impact after the 20 days of intermittence.